Endoscopic trans gluteal minimal‐invasive approach for nerve liberation (ENTRAMI technique) in case of pudendal and/or cluneal neuralgia by entrapment: One‐year follow‐up. Issue 7 (17th July 2020) - Jottard, Katleen; Bruyninx, Luc; Bonnet, Pierre; De Wachter, Stefan
Abstract: Background: Chronic neuropathic perineal pain syndrome is a collective term that encompasses several diagnoses. In patients where the neuropathic pain syndrome is caused by pudendal or cluneal nerve entrapment, surgical release can be proposed if other measures have failed. The aim of this study is to evaluate the clinical outcome of patients suffering from pudendal and/or cluneal nerve entrapment at 1 year after this minimal invasive surgery, which is based on the open trans gluteal approach who has proven its efficacy compared to medical treatment in a randomized control trial. Methods: Patients eligible for inclusion had chronic perineal neuropathic pain for at least 3 months in the area served by the pudendal and/or cluneal nerve, refractory to conservative measurements. Patients met all five of the Nantes criteria. Results: Fifteen patients underwent the ENTRAMI technique. At 1 year after surgery, overall reduction of the average maximal Numeric Pain rating Scale (NPRS‐score) was from 9 (range, 7‐10) at baseline to 5 (range, 0‐10; P ‐value <.05). At 1 year 73% of patients declared to have a "good treatment response" (patient global impression of change [PGIC] >30%) and optimal treatment response (PGIC ≥90%) was found in 40% ( P ‐value <.05). No complications were recorded. Conclusion: This study clearly shows that the technique is feasible with promising long‐term results in a difficult to manage patient group.